Fazlur Rahman Perspective On The Science Concept - Turhamun (Program Studi Pendidikan Agama Islam (PAI), 2023)
Islam requires every male and female Muslim to learn knowledge from birth to death. This is because, with science, Muslims can maintain their mandate as a caliph well. Without science, then the world will quickly break down, and man may not know how to return to his Rabb. The consequence is that acquiring knowledge must be based on a love of God and merely as a form of glorifying the greatness of His name. Fazlur Rahman, a modern scholar, finally succeeded in formulating the building of Modern Islamic Science without any scientific dichotomy. Therefore, exploring the concept of science in the point of view of fazlur rahman will greatly help the development of science itself, especially in today's modern context. The literature approach is the right choice to get the targets to be achieved related because it can accumulate information from various articles that can become a basis for information as well as material for analysis. The results showed that for Fazlur Rahman, science is knowledge obtained through learning, and the way to get it is by observation and experimentation involving the roles of the senses, reason, and heart. Then the source of knowledge for Fazlur Rahman comes from Allah Almighty with the intercession of the Qur'an, Hadith, and recorded history. The function of science is to enforce a just social system and provide solutions to the growing problems of the people.